2011
DOI: 10.1371/journal.pone.0027441
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan Extract Induces Apoptosis in MCF-7 Cells via a Mechanism Involving the ROS-Dependent JNK Activation and Mitochondria-Mediated Pathways

Abstract: BackgroundFucoidan extract (FE), an enzymatically digested compound with a low molecular weight, is extracted from brown seaweed. As a natural compound with various actions, FE is attractive, especially in Asian countries, for improving the therapeutic efficacy and safety of cancer treatment. The present study was carried out to investigate the anti-tumor properties of FE in human carcinoma cells and further examine the underlying mechanisms of its activities.Methodology/Principal FindingFE inhibits the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 56 publications
10
113
1
3
Order By: Relevance
“…This results agrees with that obtained for LMW fucoidan extracted from pheophicae cell wall increasing cell proliferation of osteoblast cells and improving bioavailability (Changotade et al 2008). Zhang et al (2011) also demonstrated that enzymatically hydrolyzed 500 Da (Kasperk et al 1995). Previous data reported that LMW fucoidan increased the cell proliferation of 7F2 cells, in order to assess whether LMW fucoidan is able to enhance osteoblast differentiation, we measured ALP and osteocalcin as the phenotype marker of the second and third stage, respectively.…”
Section: Effect Of Lmw Fucoidan and Fucoidan On Cell Viabilitysupporting
confidence: 90%
“…This results agrees with that obtained for LMW fucoidan extracted from pheophicae cell wall increasing cell proliferation of osteoblast cells and improving bioavailability (Changotade et al 2008). Zhang et al (2011) also demonstrated that enzymatically hydrolyzed 500 Da (Kasperk et al 1995). Previous data reported that LMW fucoidan increased the cell proliferation of 7F2 cells, in order to assess whether LMW fucoidan is able to enhance osteoblast differentiation, we measured ALP and osteocalcin as the phenotype marker of the second and third stage, respectively.…”
Section: Effect Of Lmw Fucoidan and Fucoidan On Cell Viabilitysupporting
confidence: 90%
“…The growth inhibition caused by fucoidan occurred in a dose-and time-dependent manner. Our findings were in agreement with studies of other cancer types [19,23]. Previous studies showed that G 0 /G 1 cell cycle arrest occurred in a non-small-cell bronchopulmonary carcinoma line and breast cancer MCF-7 cells [27,28].…”
Section: Discussionsupporting
confidence: 93%
“…[14][15][16] The immunomodulatory effects of fucoidan may be associated with the expression of pro-inflammatory cytokines along with the generation of NO and ROS. 17,18 Our previous study has established fucoidan as a novel antileishmanial agent. 19 The antileishmanial effect of fucoidan was associated with a shift from disease-promoting Th2 to disease-resolving Th1 cytokine response in conjunction with the generation of NO and ROS.…”
Section: Introductionmentioning
confidence: 99%